Characterization and Control of a Strontium Ferrite Motor - Marcos A. A. Costa; Edgar R. Braga-Filho; Antonio M. N. Lima (Eletrônica de Potência, 2015)
Exploiting the flux concentration configuration is a good alternative for designing a relatively low cost synchronous motor based on ferrite magnets. This paper discusses the design of a motor drive system based on a three-phase permanent magnet motor in which both the use of low cost ferrite and minimization of cogging torque have been adopted as design criteria. The dynamic modeling, parameter identification, and experimental characterization of the motor as well as the overall control system design have been performed. Simulation and experimental results are presented to demonstrate the correctness of the methodology and the feasibility of proposed motor drive solution and its related feedback control laws.